Enhancing Early Mathematics Learning Through an Interactive Storybook: A Development and Validation Study - Solfiah, Yeni; Nazri, Mohd; Risma, Devi; Satria, Defni; Pratiwi, Nanda; Eriani, Eva; Mastuinda, Mastuinda (Jurnal Pendidikan Progresif, 2025)
Enhancing Early Mathematics Learning Through an Interactive Storybook: A Development and Validation Study. Objective: This research aims to develop and implement an active mathematics learning paradigm for early childhood through illustrated storybooks that integrate fundamental mathematical concepts, namely numbers, patterns, geometry, measurement, and statistics. The goal is to provide a developmentally appropriate platform that encourages engagement, improves math proficiency, hones problem-solving skills, and makes learning more meaningful and enjoyable. Methods: The methodology used is a development research based on the Dick and Carey model. The validation process involved mathematicians, early childhood education experts, kindergarten educators, and media experts. Data were obtained through surveys, interviews, observations, and limited trials involving 14 children aged 5–6 years in Pekanbaru, Riau Province, Indonesia. Quantitative data analysis employed descriptive statistics, pretest-posttest comparisons, normality tests, and homogeneity tests. At the same time, qualitative data were obtained from expert evaluations and instructor comments. Findings: The validation results showed that the developed media met the criteria of validity, practicality, and efficacy, with scores from PAUD experts of 88.00%, mathematics experts of 89.33%, early childhood teachers of 81.54%, and media experts of 88.00%, with an overall category of "very good". In the limited trial stage, an average pretest score of 17.59 and a posttest score of 25.2 were obtained, indicating a significant increase in all mathematics indicators. The normality test (p > 0.05) indicated that the data were normally distributed, while the homogeneity test (p > 0.05) indicated that the data were homogeneous. The t-test results showed that the calculated t-value for all indicators was greater than the t-table value (1.771) with a significance level of 0.000 < 0.05, indicating that the media had a significant impact on improving children's mathematics abilities. Observations revealed positive responses from the children, including increased interest, focus, and active involvement. Conclusions: Active math storybooks have been recognized as an innovative learning tool for early childhood, helping educators create a stimulating learning environment and serving as an effective resource for parents. The design, which combines stories, games, and interactive activities, has been proven to strengthen children's math skills. Keywords: active learning design, early childhood, education, mathematics.